Monitoring and surveillance of genetically modified higher plants : - Kjellsson, Gosta (Birkhauser-Verlag, 2001)
Describes objectives and procedures for monitoring and surveying different types of GM plants, including herbicide tolerance, insect resistance and changed agronomic performance. This book also covers detection of GM plant dispersal and hybridisation; agricultural use and large scale effects; and habitat selection and community invasibility.